1, 2, 3‐Triazole in Heterocyclic Compounds, Endowed with Biological Activity, through 1, 3‐Dipolar Cycloadditions. Issue 16 (31st March 2014) - Lauria, Antonino; Delisi, Riccardo; Mingoia, Francesco; Terenzi, Alessio; Martorana, Annamaria; Barone, Giampaolo; Almerico, Anna Maria
Abstract: 1, 3‐Dipolar cycloaddition reactions can be considered a powerful synthetic tool in the building of heterocyclic rings, with applications in different fields. In this review we focus on the synthesis of biologically active compounds possessing the 1, 2, 3‐triazole core through 1, 3‐dipolar cycloaddition reactions. The 1, 2, 3‐triazole skeleton can be present as a single disubstituted ring, as a linker between two molecules, or embedded in a polyheterocycle. The cycloaddition reactions are usually catalysed by copper or ruthenium. Domino reactions can be achieved through dipolarophile anion formation, generally followed by cyclisation. The variety of attainable heterocyclic structures gives an illustration of the importance of the 1, 2, 3‐triazole core in medicinal chemistry. Abstract : 1, 3‐Dipolar cycloaddition reactions, uncatalysed or catalysed by transition metals, constitute a powerful synthetic tool for 1, 2, 3‐triazole derivatives, an important class of heterocyclic compounds in medicinal chemistry.